PRIORITY AND THE RIGHT OF PRIORITY IN PATENT LAW – A RIGHT WITH AN AMBIGUOUS NATURE AND SURPRISING EFFECTS - Viorel ROȘ; Andreea LIVĂDARIU (Challenges of the Knowledge Society)
Priorities and the right of priority in patent law have multiple meanings and diverse contents. They are rights with an ambiguous nature and effects that sacrifice substance in favour of form, as they are designed to ensure order, stability, and legal certainty, while also providing protection against the risk of earlier disclosures of the same invention, arising from deposits that become part of the prior art and, in the absence of recognition of such rights, can be cited and destructive of novelty. Priority can only be recognized for those elements that are clearly disclosed in the patent application taken as a whole. In other words, the scope of protection claimed in the subsequent application cannot be broader than that of the priority application. The problem, the solution, and the essential features of the invention later filed for patenting must be identical to those in the earlier application for the priority date to be validly claimed for the subsequent application. Moreover, for the priority derived from the earlier application to be accepted, the subsequent application must contain new inventive knowledge or information. If certain features of the invention in a subsequent application claiming priority are not found in any of the claims formulated in the earlier application, priority can still be recognized if these features are clearly and unambiguously derivable from the overall content of the earlier application.